2018
DOI: 10.1103/physrevlett.121.268101
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Fitness Adjustment Can Lead to Coexistence of Hierarchically Interacting Species

Abstract: Organisms that exploit different environments may experience a stochastic delay in adjusting their fitness when they switch habitats. We study two such organisms whose fitness is determined by the species composition of the local environment, as they interact through a public good. We show that a delay in fitness adjustment can lead to coexistence of the two species in a metapopulation, although the faster growing species always wins in well-mixed competition experiments. Coexistence is favored over wide param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Accordingly, such time-delay feature is different from the relative timescale of strategy and resource dynamics introduced in previous works [17,24], which characterizes the relative strength of strategic versus resource change. On the other hand, we stress that delays in fitness adjustment have been already considered by Bauer and Frey who observed a coexistence of two competing species in a metapopulation [30]. But studying the direct consequence of time delay on a renewable environment which is subject to the battle of competing consuming strategies remained unexplored.…”
Section: Introductionmentioning
confidence: 84%
“…Accordingly, such time-delay feature is different from the relative timescale of strategy and resource dynamics introduced in previous works [17,24], which characterizes the relative strength of strategic versus resource change. On the other hand, we stress that delays in fitness adjustment have been already considered by Bauer and Frey who observed a coexistence of two competing species in a metapopulation [30]. But studying the direct consequence of time delay on a renewable environment which is subject to the battle of competing consuming strategies remained unexplored.…”
Section: Introductionmentioning
confidence: 84%
“…A key factor for the dynamics is the spatial clustering of individuals, which has already been argued by Hamilton to support cooperation in populations [27], because cooperating individuals are more likely to interact with each other and therefore are less likely to be exploited by defectors. To what degree this determines the composition of a population has been studied extensively on different kinds of lattices as well as for different kinds of interaction rules [8,[10][11][12][28][29][30][31][32][33][34]. Specifically, for the snowdrift game, it was shown that accounting for spatial extension can change population ratios compared to well-mixed systems [29,35].…”
Section: B Evolutionary Games In Spatially Extended Systemsmentioning
confidence: 99%
“…In such a situation cooperators can benefit from other cooperators, and they also run a lower risk to be exploited by non-cooperating free-riders. Possible ecological scenarios promoting such an assortment include spatially extended systems [263,137,298,112,19,21,20], populations structured into distinct sub-populations [376,317,88,195,159,177,236,335,336,222] or more complex interactions between different individuals within a population (networks) [215,305,269,274,5].…”
Section: Reciprocity and Assortment Can Stabilize Cooperationmentioning
confidence: 99%
“…This suggests that in many biological scenarios, the spatial clustering of individuals cannot explain stable cooperation but additional mechanisms are necessary for spatial structure to promote the evolution of cooperation. For example, it has recently been shown that delayed adjustment to changes in the environments can affect the long-term behaviour of microbial communities and promote robust cooperation [20,21,19]. Active motility is an essential part of biological reality.…”
Section: The Role Of Bacterial Motility In Spatially Extended Systemsmentioning
confidence: 99%
See 1 more Smart Citation